Volumetric Construction: Learning from Sweden, Finland, and the United States - Michel Mounayar (Building Technology Educators’ Society, 2025)
This paper presents the findings from our research on volumetric construction, including field visits to major factory-built housing companies in Sweden, Finland, and the United States. These visits aimed to address the principal research question: Is volumetric construction a viable solution to the current housing shortage?
Keywords: building construction; volumetric construction; housing; factory built